The PEAK1–PPP1R12B axis inhibits tumor growth and metastasis by regulating Grb2/PI3K/Akt signalling in colorectal cancer. (1st February 2019) - Ding, Chenbo; Tang, Wendong; Wu, Hailu; Fan, Xiaobo; Luo, Junmin; Feng, Jihong; Wen, Kunming; Wu, Guoqiu
Abstract: Pseudopodium enriched atypical kinase 1 (PEAK1), a novel non-receptor tyrosine kinase, was recently implicated in cancer pathogenesis. However, its functional role in colorectal cancer (CRC) is not well known. Herein, we demonstrated that PEAK1 was frequently downregulated in CRC and significantly associated with tumor size, differentiation status, metastasis, and clinical stage. PEAK1 overexpression suppressed CRC cell growth, invasion, and metastasis in vitro and in vivo, whereas knockout had the opposite effects. Further evaluation revealed that PEAK1 expression was positively correlated with protein phosphatase 1 regulatory subunit 12B (PPP1R12B) in CRC cell lines and clinical tissues, and this protein was found to suppress activation of the Grb2/PI3K/Akt pathway. Moreover, PPP1R12B knockdown markedly abrogated PEAK1-mediated tumor suppressive effects, whereas its upregulation recapitulated the effects of PEAK1 knockout on cell behaviours and the activation of signalling. Mechanistically, PI3K and Akt inhibitors reversed impaired the effect of PEAK1 function on cell proliferation, migration, and invasion. Our results provide compelling evidence that the PEAK1–PPP1R12B axis inhibits colorectal tumorigenesis and metastasis through deactivation of the Grb2/PI3K/Akt pathway, which might provide a novel therapeutic strategy for CRC treatment. Highlights: PEAK1 is frequently downregulated in CRC and is associated with clinical parameters. PEAK1 suppresses CRC cell growth, invasion, and metastasis in vitro and in vivo . Expression of PEAK1 is positively correlated with PPP1R12B levels in CRC. The PEAK1–PPP1R12B axis inhibits CRC through Grb2/PI3K/Akt pathway deactivation.